The Marriage Law Reform in The Global Era: Integrating Human Rights into Family Law - I Nyoman Sujana; Nur Fareha; Jawade Hafidz; Indriana Masru’iyati Salma Izzah; Mazhab Mursida Zidan (Unissula, 2026)
The purpose of this study is to examine marriage law reform in the global era, emphasizing the integration of human rights principles into family law. This study focuses on how marriage law can respond to the demands of globalization, gender equality, and the protection of vulnerable groups. This study uses a juridical-normative approach and comparative methods through a review of laws and regulations, court decisions, and ratified international instruments. The analysis focuses on practices in Indonesia and Southeast Asian countries, particularly Malaysia and the Philippines. This study reveals that Indonesia still places religion as the primary basis for marriage legality, Malaysia faces the complexity of dualism between Islamic law and civil law, while the Philippines is relatively progressive in adopting human rights principles despite still being influenced by Catholic doctrine. This study contributes to the family law literature by offering an integrative perspective that emphasizes the importance of marriage law reform that is responsive to local values while aligning with global human rights standards. These findings have strategic implications for the development of family law policy in Southeast Asia in the face of globalization and international standardization.